2007
DOI: 10.1111/j.1399-6576.2007.01335.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐medication with intravenous clonidine suppresses fentanyl‐induced cough

Abstract: Pre-treatment with intravenous clonidine (2 microg/kg) suppressed the reflex cough induced by fentanyl, with mild hemodynamic changes. Therefore, intravenous clonidine may be a clinically useful method of suppressing fentanyl-induced cough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 18 publications
2
47
0
1
Order By: Relevance
“…In accordance with our findings, Horng et al showed that intravenous premedication with clonidine 2 mcg/kg significantly decreased the cough induced by fentanyl administration (17.3% in clonidine pretreated patients versus 38.7% in control group). This effect was associated with mild reduction in heart rate and blood pressure [9]. Similarly, in our study, vital signs were more stabled in the clonidine group than the dextromethorphan and the placebo group.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In accordance with our findings, Horng et al showed that intravenous premedication with clonidine 2 mcg/kg significantly decreased the cough induced by fentanyl administration (17.3% in clonidine pretreated patients versus 38.7% in control group). This effect was associated with mild reduction in heart rate and blood pressure [9]. Similarly, in our study, vital signs were more stabled in the clonidine group than the dextromethorphan and the placebo group.…”
Section: Discussionsupporting
confidence: 52%
“…Fentanyl-induced cough could also be the result of a mechanical or chemical stimulation of sensory receptors within the respiratory tract; the afferent impulses from these receptors may activate a putative brainstem cough center [7]. Drugs such as ketamine, terbutaline, clonidine, dexamethasone, and lidocaine as well as performing some maneuvers such as a forced expiration against open glottis, dilution of fentanyl to 10 μg/ ml, and prolonged injection time have all been evaluated in reducing this fentanyl induced cough [8][9][10][11][12][13]. Dextromethorphan is an antitussive drug that is used for suppression of cough caused by minor throat and tracheo-bronchial irritation, especially after inhalation of any irritants.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown in ASA I-III nonsmoking European patients that the incidence of cough after 1.5 g . kg -1 fentanyl is around 4% and not related to the speed of injection [1], much lower than previously assumed [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 84%
“…Since a longer observation period in all likelihood should result in a higher rather than a lower incidence of cough by chance alone this also can be excluded as an explanation for the higher incidence of cough in the study by Lin et al Thus racial differences of the subjects studied (Chinese vs. European people) seemed to be the most likely explanation for the different incidences of cough between the study by Lin et al compared to our study. In fact, in an asiatic or chinese population [2,3,6,7,9] intravenous injection of fentanyl in doses ranging from 2-5 g . kg -1 given within 1-5 seconds evoked cough in 28-65% in contrast to 3% incidence after 7 5 g .…”
Section: Discussionmentioning
confidence: 99%
“…I remain perplexed that researchers see so much of this problem, and wondered whether it was simply that they were using a higher dose of fentanyl compared to mine, but several of the papers these groups cite [5][6][7][8] used no more than 2 lg.kg )1 and still reported similar incidences.…”
mentioning
confidence: 99%